1994
DOI: 10.1590/s0074-02761994000100008
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi infection in the opossum Didelphis marsupialis: absence of neonatal transmission and protection by maternal antibodies in experimental infections

Abstract: The high rate of natural Trypanosoma cruzi infection found in opossums does not always correlate with appreciable densities of local triatomid populations. One alternative method which might bypass the invertebrate vector is direct transmission from mother to offspring. This possibility was investigated in five T. cruzi infected females and their litters (24 young). The influence of maternal antibodies transferred via lactation, on the course of experimental infection, was also examined. Our results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 0 publications
0
17
0
2
Order By: Relevance
“…Vertical transmission (including infections acquired congenitally and during lactation) and horizontal transmission (through urine or anal gland secretions) appear to be very unlikely routes of infection in Didelphis sp. (Jansen et al, 1994;Grisard et al, 2000;Telford and Tonn, 1982;Travi et al, 1994). The observed ageprevalence curves in opossums, increasing with time of exposure (age) after weaning, are consistent with vector-mediated transmission.…”
Section: Discussionmentioning
confidence: 63%
“…Vertical transmission (including infections acquired congenitally and during lactation) and horizontal transmission (through urine or anal gland secretions) appear to be very unlikely routes of infection in Didelphis sp. (Jansen et al, 1994;Grisard et al, 2000;Telford and Tonn, 1982;Travi et al, 1994). The observed ageprevalence curves in opossums, increasing with time of exposure (age) after weaning, are consistent with vector-mediated transmission.…”
Section: Discussionmentioning
confidence: 63%
“…Each number signifies one isolate for each golden lion tamarin especimen. Lanes 1 to 9 correspond to isolates of animals 583, 291, 310, 385, 493, 584, 593, 633 and 592. of T. cruzi is rare among humans and other mammalian orders including Marsupialia (Jansen et al 1994). Infection of free-ranging tamarins with T. cruzi probably occurs by contamination with the feces of infected triatomine bugs, since these primates do not include hemipterans in their diet Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that maternal antibodies transferred during lactation could probably confer protection to young P. opossum in the pouch, since newly weaned animals control this parasitism in experimental infections as do naturally infected young animals. It has been reported that marsupials acquire antibodies only a few hours after suckling for the first time (Hindes & Mizell 1976), and that D. marsupialis maternal antibodies confer partial protection to the young (Jansen et al 1994).…”
Section: Discussionmentioning
confidence: 99%